Advances in the pathogenesis of primary and secondary haemophagocytic lymphohistiocytosis: differences and similarities. (5th June 2016) - Brisse, Ellen; Wouters, Carine H.; Matthys, Patrick
Summary: Haemophagocytic lymphohistiocytosis (HLH) comprises a heterogeneous spectrum of hyperinflammatory conditions that are inherited (primary HLH) or acquired in a context of infections, malignancies or autoimmune/autoinflammatory disorders (secondary HLH). Genetic defects in the cytotoxic machinery of natural killer and CD8 + T cells underlie primary HLH, with residual cytotoxicity determining disease severity. Improved sequencing techniques have expanded the range of causal mutations and have redefined many cases of secondary HLH as primary HLH and vice versa, blurring the distinction between both subtypes. These insights allow HLH to be conceptualized as a threshold disease, in which interplay between various genetic and environmental factors causes progressive inflammation into a critical point, beyond which uncontrolled activation of immune cells and excessive cytokine production give rise to the cardinal symptoms of HLH. Various pathogenic pathways may thus converge to a common end stage of fulminant HLH.